A performance monitoring system with the capability of detecting anomalies for corporate business intelligence reporting systems - Yalçın, Serap (My University, 2022)
Business Intelligence plays a key role in corporate companies to make managerial decisions. Especially for larger ones, Business Intelligence reporting systems get more complex with their large amount of data. When the number of reports increased, the performance of the reporting system might be a more important issue. Failures that may arise in reporting systems may disrupt the decision making processes of corporate companies. Therefore, it is necessary to understand better the Business Intelligence reporting system to capture the problems quickly. In this study, a system is established to monitor the performance of Business Intelligence reporting system of a Bank, with the capability of detecting anomalies. With this system, it is aimed to facilitate the monitoring of the reporting environment and to detect and prevent problems that may arise in the environment. For anomaly detection, the data are collected from reporting environment and analyzed. The collected data are trained with different Machine Learning models and the best fitted model is integrated into the performance monitoring system. In this performance monitoring system, many indicators of the business intelligence reporting system are integrated into the established system and presented to the employees as a new report. With this system integrated into the bank, employees can follow the Business Intelligence reporting environment more easily.

İş Zekası uygulamaları veriyi anlamlı hale getirmek için kullanılan yaygın yöntemlerden biridir. Aynı zamanda, kurumsal şirketlerde yönetimsel kararlar alma konusunda kilit bir rol oynamaktadır. Kurumsal firmalarda, toplanan veri miktarı arttıkça raporlama yapmak da zorlaşmaktadır. Özellikle büyük firmalar için, İş Zekası raporlama sistemlerindeki rapor sayısının da artması ile raporlama sisteminin performansı daha önemli bir konu haline gelmektedir. Raporlama sistemlerinde çıkabilecek aksaklıklar, kurumsal firmaların karar alma süreçlerini sekteye uğratabilir. Bu nedenle, sistemdeki sorunları hızlı bir şekilde yakalamak için İş Zekası raporlama sistemini daha iyi anlamak ve sistemi kontrol edebiliyor olmak gereklidir. Bu çalışmada, bir bankanın İş Zekası raporlama sisteminin performansını izleyebilmek ve sistemdeki anormallikleri tespit edebilmek için yeni bir performans izleme sistemi kurulmuştur. Bu sistem ile raporlama ortamının takibini kolaylaştırmak ve ortamda çıkabilecek sorunları önceden tespit ederek engelleyebilmek amaçlanmıştır. Anormallik tespiti için raporlama ortamına ait veriler toplanarak analiz edilmiş ve toplanan veriler farklı Makine Öğrenmesi modelleri ile tahminlenerek en başarılı olan model performans izleme sistemine entegre edilmiştir. Bu performans izleme sisteminde, iş zekası raporlama sistemine ait pek çok gösterge, kurulan sisteme entegre edilerek yeni bir rapor halinde İş Zekası raporlama sisteminden sorumlu çalışanların kullanımına sunulmuştur. Bankaya entegre edilen bu sistem ile çalışanlar İş Zekası raporlama sistemini daha rahat takip edebilir duruma gelmişlerdir.
Keywords: Anomali Tespiti; Anomaly Detection; Bilgisayar mühendisliği; Business Intelligence; Computer engineering; Data Mining İş Zekası; OLAP; Performance Monitoring; Performans İzleme; SSAS; Veri Madenciliği